Water reuse: A review of recent international contributions and an agenda for future research - David Saurí; Ana Arahuetes (Documents d'Anàlisi Geogràfica, 2019)
Wastewater treatment and the generation of recycled water for eventual reuse are raising important expectations worldwide as a resource of interest to solve future water needs. In this review, we first acknowledge the important technical advances made in relation to wastewater treatment although we also point out some of the current challenges faced by wastewater treatment technology, most especially new families of pollutants linked to pharmaceuticals and home consumer products. Most of the review highlights the main points of research on the perception of recycled water and the determinants of its public acceptance in the social and psychological literature with an emphasis on the so-called ‘yuck factor’. The review also identifies several areas for future research relating recycled water with social territorial and environmental issues.